PENINGKATAN HASIL BELAJAR MATERI BANGUN DATAR MELALUI MODEL TEAM ASSISTED INDIVIDUALIZATION DI KELAS IV B SD NEGERI 47 KOTA JAMBI - Heni Maladewi (Universitas Syiah Kuala, 2019)
To be able to learn something well, we need to hear, see, ask questions about it, and discuss itwith others. Not only that, students need to